Pengaruh Gaya Hidup Dan Motivasi Belajar Terhadap Prestasi Belajar Mata Pelajaran Pendidikan Kewarganegaraan - Mimi Fianora (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2019)
This study aims to analyze empirically the influence of lifestyle and learning motivation on Civic Education achievement of SMAN 1 Kec. Salimpaung Kabupaten Tanah Datar students. This type of research is causative research. The population in this study were all students of SMAN 1 Kec. Salimpaung Kabupaten Tanah Datar. The sample was chosen randomly as many as 23 students in class XII. The data used in the study are primary data derived from randomly distributed questionnaires. This study uses multiple regression analysis with SPSS 21 software. The results of the study indicate that lifestyle variables (X1) have a significant positive effect on student learning achievement (Y). Learning motivation variable (X2) has no significant effect on student learning achievement.